Efektivitas Penerbitan Sertifikat Mutu dan Keamanan Hasil Perikanan (SMKHP) di Badan Pengendalian dan Pengawasan Mutu Hasil Kelautan dan Perikanan Kupang, Nusa Tenggara Timur - Rahardian, Mydan Amlang; Suseno, Suseno; Lailatussifa, Rr. Radipta; Effendi, Achmad (Innovative: Journal Of Social Science Research, 2025)
Export is an activity of sending services or goods for sale or trade. This activity is part of international trade and can involve various types of products. In the implementation of exports, there are several document requirements that must be completed. One of them is the Certificate of Quality and Safety of Fishery Products (SMKHP). In the field of fisheries, SMKHP is one of the important documents supporting export activities. Without SMKHP, fishery products will be difficult to export. This study aims to determine the effectiveness of the Marine and Fishery Product Quality Control and Supervision Agency in implementing the procedure for issuing the Certificate of Quality and Safety of Fishery Products. In its implementation, it is required to carry out surveillance activities. Where surveillance is an activity carried out by conducting inspections/monitoring of a company. Several stages that must be passed in issuing the Certificate of Quality and Safety of Fishery Products are: filling out the application form for issuing the SMKHP, filling out the packaging detail form, filling out the document requirement details, filling out the container detail form, inspection by the exporter/UPI, and issuing the SMKHP. Each stage is carried out through the PPK Online website, both from the company and the Marine and Fisheries Product Quality Control and Supervision Agency using SisterKaroline. The results of the study indicate that the implementation of the SMKHP issuance procedure carried out by the Marine and Fisheries Product Quality Control and Supervision Agency has been carried out effectively and the sustainability of exports has not experienced any obstacles.